Non-distorted visible light-absorbing thiol-PEGylated gold-coated superparamagnetic iron oxide nanoparticles–porphyrin conjugates and their inhibitory effects against nosocomial pathogens. (December 2019) - Amos-Tautua, Bamidele M.; Fakayode, Olayemi J.; van Vuuren, Sandy; Songca, Sandile P.; Oluwafemi, Oluwatobi S.
Abstract: Abstract : A low-cost synthesis approach was developed for the fabrication of four symmetric meso-substituted water-soluble thiolated polyethylene glycol gold-coated superparamagnetic iron oxide nanoparticles–porphyrin (p-hydroxyphenyl [THPP], 3, 5-dimethoxyphenyl [TdMPP], 3-pyridyl[T-3-PyP], and 1-methylpyridinium-3-yl[T3-Py + P4I − ]) conjugates to achieve materials with enhanced absorption and therapeutic properties. After evaluation of their antibacterial inhibition characteristics against four nocosomial pathogens ( Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Enterococcus faecalis ), THPP and TdMPP conjugates showed some remarkable minimum inhibitory concentration values of 0.104 and 0.625 mg/mL against E. coli and E. faecalis, respectively, making these materials to be alternative agents for the inhibition of these pathogens in the environmental and clinical fields.